PENINGKATAN KETERAMPILAN BERHITUNG SISWA MELALUI MEDIA KOTAK AJAIB BERBASIS STEM PADA MATERI KONSEP PENJUMLAHAN - anik, anik twiningsih (Jurnal Pendidikan Dasar, 2020)
This study aims to determine the improvement of student learning outcomes through the media ko Ajib (Magic Box) Based on STEM (Science, Technology, Engineering, Mathematics) in the concept of addition material. This research was conducted with research subjects to class I students in one of the Public Elementary Schools in Surakarta City in the first semester of 2018/2019 academic year as many as 24 students, consisting of 7 male students and 17 female students. The method used in this study is Classroom Action Research with patterns: planning, implementation, observation, reflection, revision. Data collection techniques using the method of discussion, observation, tests, field notes and documentation. From the results of the study it was found that student learning outcomes had increased from cycle I to cycle II, namely, cycle I (70.83%), cycle II (91.66%). The conclusion of this study is through the use of Ko Ajib teaching aids (Magic Box) based on STEM (Science, Technology, Engineering, Mathematics) on the summing concept material can improve learning outcomes of first grade students of Public Elementary Schools in Surakarta City Semester I Academic Year 2018 / 2019